Author Correction: Sculpting nanoparticle dynamics for single-bacteria-level screening and direct binding-efficiency measurement (Nature Communications, (2018), 9, 1, (815), 10.1038/s41467-018-03156-5) - Shi, Y.Z. (Nature Publishing Group, 2021)
10.1038/s41467-019-09171-4